Availability and Usability of Screen Reading Software by Students with Visual Impairment – Current Scenario - Dheesha, J.B. (Indian Journal of Educational Technology, 2020)
Assistive technology plays a vital role in the education of students with disabilities and it also paves way for their independent living. Students with visual impairment have difficulty in accessing visual materials. Assistive technology helps students with visual impairment to access the general curriculum and improve their academic performance. The Optical Braille Recognition (OBR) software, Job Access with Speech (JAWS) software, Non Visual Desktop Access (NVDA) software are available and they help the students with visual impairment to read Braille documents, scan the Braille documents, translate the text to Braille and read text materials on the computer screen. The objective of this study is to find out the availability and usability of screen reading software by students with visual impairment. Totally 30 students with visual impairment from integrated and inclusive schools from Coimbatore District were selected as a samples. The result shows that availability and usability of software by students with visual impairment is very low. It may be because of the non-availability of screen reading software in the schools. It also shows that the special educators and general educators lack knowledge in using screen reading software to teach students with visual impairment.